Social Entrepreneurship - A Review and a Proposal of New Integrated Framework - Venkoba Rao; Tahseen Anwer Arshi; Swapnil Morande (Kurdish Studies, 2024)
The study systematically reviews 149 articles on Social Entrepreneurship (SE) published between the years 2005-2021 and proposes an integrative "Characteristics-Context-Consequences" (CCC) framework. The thematic analysis revealed that social entrepreneurs' characteristics, supported by traditional entrepreneurship skills, relate to social empathy, problem-solving, and social capital building. Additionally, various contexts, such as institutional support, the innovation ecosystem, and social legitimacy, largely determine the success of SE endeavors. SE characteristics and contexts drive the consequences of social innovation, social change, and social and economic well-being.